Resolving verbal reduplication paradoxes in Malawian Tonga - Mkochi, Winfred (Stellenbosch Papers in Linguistics Plus, 2017)
The paper describes three verbal reduplication paradoxes in Malawian Tonga, a southern Bantu language spoken in the northern part of Malawi. RED exhibits characteristics of being either total or partial and being prefixed or suffixed to the Base. The problem of whether the relevant level of prosodic (reduplicative) stem analysis is the syllable or the mora and, thus, whether the minimal size of RED should be two syllables or two moras, is considered. The paper argues that this language offers three possibilities for reduplication namely, partial prefixal reduplication, total suffixal reduplication, and partial suffixal reduplication. Thus, the language takes optionality between prefixal and suffixal reduplication, although the latter appears to be the default one. The paper also argues that the relevant unit of Prosodic Stem analysis is, typically, the syllable and that reduplicative Prosodic Stems, like the Base stem, are therefore required to be minimally bisyllabic, like in many other Bantu languages.